A new species of Leptobrachella (Anura: Megophryidae) from southern Guangxi, China - Chen, Weicai; Liao, Xiaowen; Zhou, Shichu; Mo, Yunming (Zootaxa, 2019)
This study describes a new member of the genus Leptobrachella, Leptobrachella shangsiensis sp. nov., based on morphological, acoustic and molecular analyses from southern Guangxi, China. L. shangsiensis sp. nov. differs from its congeners by a combination of the following characters: (1) SVL 24.9–29.4 mm in 11 males and 30.8–35.9 mm in 5 females, (2) black supratympanic fold with dark reddish rim, (3) ventrolateral glands distinct, forming a broken line, (4) ventral surface yellowish creamy-white with marble texture, (5) iris copper in the upper and silver in the lower fifth and (6) toe webbing basal and narrow lateral fringes. The male advertisement call of L. shangsiensis sp. nov. consists of one note per call, lacking an introductory note, with a mean dominant frequency of 5.5–6.5 kHz at the ambient temperature of 21.5ºC. Uncorrected sequence divergences between L. shangsiensis sp. nov. and all homologous DNA sequences available for the 16S rRNA gene were found to be > 5.9%. L. shangsiensis sp. nov. occurs in an evergreen forest in Shiwandashan National Nature Reserve located at an elevation of 450–550 m.